Exploring Unexplored Territory: A Study of Sports Sponsorship Effectiveness in the Saudi Football League - Almaiman, Khaled; Aleid, Aayad; Alofan, Fahad; Alhumaidan, Abdullah; Al oraini, Badrea (مجلة العلوم الإدارية و الإقتصادية, 2025)
This study examines the effects of sports sponsorship on consumer behavior within Saudi Arabia’s football scene, focusing on Al Hilal FC and Tania sponsorship agreement. Utilizing a cross-sectional design with 190 participants collected via convenience sampling and social media, the data were analyzed using partial least squares structural equation modeling. Findings indicate that team identification and performance significantly enhance sponsorship awareness, which positively influences brand attitudes and purchase intentions. This research provides new insights to sports sponsorship literature by exploring its effectiveness in an unexplored context. The findings offer practical implications for brands, suggesting deeper integration with team narratives and leveraging the collectivist culture of Saudi Arabian fans to build emotional connections. By fostering meaningful engagements and supporting initiatives that resonate with the fan base’s values, brands can maximize the impact of their sponsorships.